Fern distributional records in Christensenia (Marattiaceae), Dipteris (Dipteridaceae), and Rheopteris (Pteridaceae) from the upper Sepik of Papua New Guinea - Takeuchi, Wayne (Phytotaxa, 2013)
Christensenia (Marattiaceae) is recorded for the island of New Guinea, removing a puzzling disjunction in its documented distribution. The rarely seen Rheopteris cheesmaniae (Pteridaceae), previously represented by three specimens, is rediscovered in Sepik habitats far inland from the historical north-coastal localities. Population updates are also provided for Dipteris lobbiana (Dipteridaceae), a species found throughout Malesia but otherwise known in New Guinea only from the upper Sepik. All three ferns are surprisingly common at their new sites of occurrence.